Bio-membrane based integrated systems for nitrogen recovery in wastewater treatment: Current applications and future perspectives. (February 2021) - Ye, Yuanyao; Ngo, Huu Hao; Guo, Wenshan; Chang, Soon Woong; Nguyen, Dinh Duc; Varjani, Sunita; Ding, An; Bui, Xuan-Thanh; Nguyen, Dan Phuoc
Abstract: Nitrogen removal is crucial in wastewater treatment process as excessive nitrogen content could result in eutrophication and degradation of aquatic ecosystems. Moreover, to satisfy the fast-growing need of fertilizers due to an increase in human population, recovering nitrogen from wastewater is of the most sustainable approach. Currently, the membrane technique integrated with biological processes namely bio-membrane based integrated system (BMIS) is a promising technology for recovering nitrogen from wastewater, including osmotic membrane bioreactors, bioelectrochemical systems and membrane photobioreactors. In this review study, the nitrogen recovery in different BMHSs, the role of operational parameters and the nitrogen recovery mechanism were discussed. Apart from this, the implementation of nitrogen recovery at pilot- and full-scale was summarized. Perspectives on the major challenges and recommendations of the BMIS for the nitrogen recovery in wastewater treatment were proposed, in which the integrated technologies and more scale-up studies regarding nitrogen recovery by the BMISs were also highlighted and recommended. Highlights: The N recovery by bio-membrane based integrated systems (BMISs) was discussed. Various configurations of BMISs for N recovery were reviewed. Current implementation of N recovery at pilot/full-scale was summarized. Perspective on BMISs for N recovery was given. Integrated bio-membrane hybrid systems are promising for N recovery.